First reports of esophageal adenocarcinoma with white globe appearance in Japanese and Caucasian patients - Tonai, Yusuke; Ishihara, Ryu; Yamasaki, Yasushi; Kanesaka, Takashi; Yamamoto, Sachiko; Akasaka, Tomofumi; Hanaoka, Noboru; Takeuchi, Yoji; Higashino, Koji; Uedo, Noriya; Tomita, Yasuhiko; Iishi, Hiroyasu (Endoscopy International Open, 2016)
Background and study aims: Better endoscopic diagnosis in case of Barrett’s esophagus is still needed. White globe appearance (WGA) is a novel endoscopic marker for gastric adenocarcinoma, with high sensitivity for differentiating between gastric cancer/high-grade dysplasia and other lesions. We report 2 cases of esophageal adenocarcinoma with WGA. In Case 1, esophagogastroduodenoscopy (EGD) revealed a 10-mm esophageal adenocarcinoma in a 48-year-old Japanese woman with short-segment Barrett’s esophagus. A small (< 1 mm) white globular lesion, typical of WGA, was observed under the epithelium by magnifying narrow-band imaging. A dilated neoplastic gland with eosinophilic material and necrotic epithelial fragments was identified at the site of the WGA by histologic examination. In Case 2, EGD revealed a 5-mm esophageal adenocarcinoma in a 60-year-old Caucasian man with long-segment Barrett’s esophagus. A typical WGA was observed by magnifying narrow-band imaging and similar histologic findings were identified at the site of the WGA. WGA could be a reliable endoscopic finding for target biopsy in esophageal adenocarcinoma, if its specificity is as high as in gastric cancer. The clinical implications of WGA in patients with Barrett’s esophagus should be investigated further.